Gibberellins Inhibit Nodule Senescence and Stimulate Nodule Meristem Bifurcation in Pea (Pisum sativum L.) - Serova, Tatiana A.; Tsyganova, Anna V.; Tikhonovich, Igor A.; Tsyganov, Viktor E. (Frontiers in Plant Science, 2019)
The development of nitrogen-fixing nodules formed during Rhizobium-legume symbiosis is strongly controlled by phytohormones. In this study, we investigated the effect of gibberellins (GAs) on senescence of pea (Pisum sativum) symbiotic nodules. Pea wild-type line SGE, as well as corresponding mutant lines SGEFix−-1 (sym40), SGEFix−-2 (sym33), SGEFix−-3 (sym26), and SGEFix−-7 (sym27), blocked at different stages of nodule development, were used in the study. An increase in expression of the GA2ox1 gene, encoding an enzyme involved in GA deactivation (GA 2-oxidase), and a decrease in the transcript abundance of the GA20ox1 gene, encoding one of the enzymes involved in GA biosynthesis (GA 20-oxidase), were observed in analyzed genotypes during nodule aging. A reduction in the amount of bioactive GA3 was demonstrated by immunolocalization in the early senescent mutant and wild-type lines during aging of symbiotic nodules. Down-regulated expression of senescence-associated genes encoding cysteine proteases 1 and 15a, thiol protease, bZIP transcription factor, 1-aminocyclopropane-1-carboxylate (ACC) synthase, ACC oxidase, and aldehyde oxidase was observed in the nodules of wild-type plants treated with exogenous GA3 relative to the untreated plants. GA3-treated plants also showed increases in nodule size and the nitrogen fixation zone, and decreases in the number of nodules and the senescence zone. Immunogold localization revealed higher levels of GA3 in the peribacteroid spaces in symbiosomes than in the matrix of infection threads. Furthermore, a decrease in GA3 label in mature and senescent symbiosomes in comparison with juvenile symbiosomes was observed. These results suggest a negative effect of GAs on the senescence of the pea symbiotic nodule and possible involvement of GAs in functioning of the mature nodule. Simultaneously, GA3 treatment led to nodule meristem bifurcation, indicating a possible role of GAs in nodule meristem functioning.